Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1177/2048872614527837
|View full text |Cite
|
Sign up to set email alerts
|

Value of syncope in patients with high-to-intermediate risk pulmonary artery embolism

Abstract: The history of syncope in patients with suspected PE should be considered as a possible criterion of high risk of fatal complications of in-hospital period due to frequent embolism of the pulmonary trunk and its main branches. The use of thrombolytic therapy showed a tendency in improving outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 29 publications
0
29
0
8
Order By: Relevance
“…Our study showed statistically significant differences between clinical features of "massive" aPE compared with the "non-massive" PE group. Some symptoms such as syncope, dyspnea, weakness, chest pain, cough, fever, or hemopthysis can occur in both groups, but some of them are detected more often when emboli have obstructed the pulmonary trunk or its main branches (8). We noticed that syncope, dyspnea, and weakness more often occurred in the "massive" PE group whereas cough, chest pain and fever in the "non-massive" group.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our study showed statistically significant differences between clinical features of "massive" aPE compared with the "non-massive" PE group. Some symptoms such as syncope, dyspnea, weakness, chest pain, cough, fever, or hemopthysis can occur in both groups, but some of them are detected more often when emboli have obstructed the pulmonary trunk or its main branches (8). We noticed that syncope, dyspnea, and weakness more often occurred in the "massive" PE group whereas cough, chest pain and fever in the "non-massive" group.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, near 40% of cases of aPE and DVT are prone to recur (4,7). The prognosis for aPE depends on many factors, such as individual response, the size and location of the clot, and comorbidities (8). Traditionally, massiveness of aPE has been defined on the basis of angiographic burden of emboli by use of the radiologic indexes designed for PE severity, such as Qanadli, Miller, or Mastora score (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…However, thrombolytic use was much lower in the scale of all patients with 5.6%. Duplyakov et al pointed out that thrombolytic therapy was used in 21 (60%) of 35 patients. Although syncope is not a criterion for thrombolytic therapy alone, aggressive therapy suggests a group of patients to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Duplyakov et al reported 23.8% of patients (19/80) those who classified in intermediate risk group according to ESC model (without a division into low‐risk or high‐risk) had syncope. Also, in this study, syncope rate was higher (29.9%) than that of the other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Their candidates for home care were low risk on the PE Severity Index and lacked the following contraindications, which parallel our own: hypoxemia, hypotension, active bleeding, high risk of bleeding, pregnancy, severe renal failure, barriers to adherence and follow up, and non-PE diagnoses requiring inpatient care. We drew from other studies of PE risk assessment and outpatient management to expand our list of relative contraindications to include right ventricular dysfunction (18,26,30,32,33) and syncope (20,41), two of the most common contraindications in our cohort.…”
Section: Original Researchmentioning
confidence: 99%